Clinical, radiological, and genetic characteristics of 16 patients with ACO2 gene defects: Delineation of an emerging neurometabolic syndrome. Issue 2 (28th January 2019) - Sharkia, Rajech; Wierenga, Klaas J.; Kessel, Amit; Azem, Abdussalam; Bertini, Enrico; Carrozzo, Rosalba; Torraco, Alessandra; Goffrini, Paola; Ceccatelli Berti, Camilla; McCormick, M. Eileen; Plecko, Barbara; Klein, Andrea; et al.
Abstract: Mitochondrial aconitase is the second enzyme in the tricarboxylic acid (TCA) cycle catalyzing the interconversion of citrate into isocitrate and encoded by the nuclear gene ACO2. A homozygous pathogenic variant in the ACO2 gene was initially described in 2012 resulting in a novel disorder termed "infantile cerebellar retinal degeneration" (ICRD, OMIM#614559). Subsequently, additional studies reported patients with pathogenic ACO2 variants, further expanding the genetic and clinical spectrum of this disorder to include milder and later onset manifestations. Here, we report an international multicenter cohort of 16 patients (of whom 7 are newly diagnosed) with biallelic pathogenic variants in ACO2 gene. Most patients present in early infancy with severe truncal hypotonia, truncal ataxia, variable seizures, evolving microcephaly, and ophthalmological abnormalities of which the most dominant are esotropia and optic atrophy with later development of retinal dystrophy. Most patients remain nonambulatory and do no acquire any language, but a subgroup of patients share a more favorable course. Brain magnetic resonance imaging (MRI) is typically normal within the first months but global atrophy gradually develops affecting predominantly the cerebellum. Ten of our patients were homozygous to the previously reported c.336C>G founder mutation while the other six patients were all compound heterozygotes displaying 10 novel mutations of whom 2 were nonsense predicting a deleterious effect on enzyme function. Structural protein modeling predicted significant impairment in aconitase substrate binding in the additional missense mutations. This study provides the most extensive cohort of patients and further delineates the clinical, radiological, biochemical, and molecular features of ACO2 deficiency.